2018
DOI: 10.1177/1521025118768055
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Gaps in First-Year Outcomes Between Hispanic First-Generation College Students and Their Peers: The Role of Accelerated Learning and Financial Aid

Abstract: Hispanic students are the most likely out of all racial or ethnic groups to be first-generation college students (FGCS). Hispanic FGCS have been shown to be the least likely to persist out of all racial or ethnic backgrounds. However, there is little literature on this population. To address this, the present study investigated the association of accelerated learning in high school (e.g., Advanced Placement courses and dual enrollment) and financial aid on academic outcomes for Hispanic FGCS and Hispanic non-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…First of all, the data revealed that a greater percentage of ethnic and cultural minorities were prospective first-generation college students compared to their White peers, echoing prior studies (Lohfink & Paulsen, 2005; Redford & Hoyer, 2017). In particular, recent data (Latino et al, 2020) showed that Hispanic students account for a substantial part of the first-generation student population in the United States, and this aligned with my sample. Regarding gender, the ratio of female students is higher in prospective first-generation than continuing-generation students, particularly among Black students as compared to Hispanic students.…”
Section: Discussionsupporting
confidence: 85%
“…First of all, the data revealed that a greater percentage of ethnic and cultural minorities were prospective first-generation college students compared to their White peers, echoing prior studies (Lohfink & Paulsen, 2005; Redford & Hoyer, 2017). In particular, recent data (Latino et al, 2020) showed that Hispanic students account for a substantial part of the first-generation student population in the United States, and this aligned with my sample. Regarding gender, the ratio of female students is higher in prospective first-generation than continuing-generation students, particularly among Black students as compared to Hispanic students.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, when considering all three identities, research has demonstrated that Hispanic FGCS tend to have lower family SES compared to Hispanic non-FGCS (Kouyoumdjian et al, 2017). These students may experience both academic and interpersonal stress from encountering financial challenges, lack of university experience, and academic unpreparedness (Latino, 2020;McCarron & Inkelas, 2006). Therefore, it is critical to examine how these identities, individually and in combination, contribute to students' stress.…”
Section: Intersectionality Of Identities/interaction Of Factorsmentioning
confidence: 99%
“…In general, older groups are held to higher standards of effectiveness. Having the same domains, components, and subcomponents across the age groups should help to promote longitudinal research as well as applications in education and work settings by emphasizing continuity of terminology and more clearly delineated developmental progressions (for a detailed description of the development of behavior PLDs, refer to Latino et al, 2017).…”
Section: The Act Behavioral Skills Framework (Bsf)mentioning
confidence: 99%
“…Finally, when it comes to alignment, the authors set out to design a framework that would be aligned across developmental stages and across settings by creating a system that, at the most specific level of the framework, is based on performance level descriptors (PLDs) that describe in detail what students and employees need to know and be able and willing to do in order to achieve educational and career success. From one developmental group to another and across applied contexts, the constructs and definitions remained the same and the authors used SMEs to describe what effective behavior looked like for each construct and each developmental group (see Latino et al, 2017). Thus, the BSF was designed with alignment from the onset.…”
Section: Future Considerations For Personality and Behavioral Skills ...mentioning
confidence: 99%